A One Health approach to child stunting: Evidence and research agenda - Gharpure, R.; Mor, Siobhan M.; Viney, M.; Hodobo, T.; Lello, J.; Siwila, J.; Dube, K.; Robertson, R.C.; Mutasa, K.; Berger, C.N.; Hirai, M.; Brown, T.; et al. (American Society of Tropical Medicine and Hygiene, 2021)
Stunting (low height for age) affects approximately one-quarter of children aged < 5 years worldwide. Given the limited impact of current interventions for stunting, new multisectoral evidence-based approaches are needed to decrease the burden of stunting in low- and middle-income countries (LMICs). Recognizing that the health of people, animals, and the environment are connected, we present the rationale and research agenda for considering a One Health approach to child stunting. We contend that a One Health strategy may uncover new approaches to tackling child stunting by addressing several interdependent factors that prevent children from thriving in LMICs, and that coordinated interventions among humans, animals, and environmental health sectors may have a synergistic effect in stunting reduction.